The Relationship Between Hip Range of Motion and Pitching Kinematics Related to Increased Elbow Valgus Loads in Collegiate Baseball Pitchers: A Pilot Study - Giorgio Zeppieri Jr. (North American Sports Medicine Institute, 2021)
# Background